Parent perceptions of motor competence in children with charge syndrome - Pamela Beach; Alexandra Stribing; Melanie Perreault; Lauren Lieberman (European Journal of Adapted Physical Activity, 2021)
CHARGE Syndrome (CS) is a low incidence disorder with unique characteristics including deafblindness, growth deficiencies, heart defects, and atresia choanae. The purpose of this study was to examine parents' perceptions of motor competence in their child with CS as well as the value and support they provide on motor competence compared to parents of children without disabilities. Parents of 33 children with CS (Mage = 6.8 years SD=2.6) and parents of 38 peers without disabilities (Mage = 7.0 years SD=2.3) completed a demographic and a 32-item parents' perception questionnaire regarding their confidence in their child's motor competence. From the results there were significantly lower motor competence scores in parents' ratings of children with CS; however, they participated with their child in movement skills and tracked their child's movement skills more often than parents of children without disabilities. No group differences were found in the belief that their child can change their movement skills, or in the importance of motor competence. These findings will assist in the understanding of the impact of parenting a child with CS upon their perception of their child's motor competence and the level of support they provide their child. This information indicates the important role that parents of children with severe disabilities have in their child's motor development.